Left ventricular myocardial and cavity velocity disturbances are stronger predictors of stress induced ischaemia in patients with significant coronary artery disease. (3rd October 2022) - Bytyci, I; Alves, L; Lopes, L; Henein, M Y
Abstract: Background and aim: Dobutamine stress echocardiography (DSE) is a well-established non-invasive investigation for significant coronary artery disease (CAD). The aim of this study was to evaluate the accuracy of cardiac Doppler parameters in predecting CAD. Methods: We prospectively studied 103 consecutive patients with suspected CAD based on typical symptoms, 59 proved to have CAD and 44 patients proved to have no-CAD (n=44). All patients underwent a complete stress Doppler echocardiographic examination, including tissue Doppler, long axis velocities and total isovolumic time (T-IVT) as a marker of cavity dyssynchrony, determined as [60 − (total ejection time (ET) + total filling time (FT))]. The wall motion score index (WMSI) was also calculated. Results: CAD patients were older, had less females, less prevalent cardiac risk factors and higher CT calcium score compared to patients with no-CAD (p<0.05, for all). At peak dobutamine stress the compromised LV longitudinal excursion (MAPSE), systolic septal and lateral velocities (s'), TAPSE and diastolic indices were more pronounced in the CAD patients compared to those without CAD, but LV dimension did not differ between groups (p>0.05). The WMSI was higher and t-IVT more prolonged in patients with CAD (p<0.01, for both). Similarly, the changes were more pronounced in patients with significant CAD compared to insignificant CAD. On multivariate model, delta mean s' OR 2.016 (1.610–3.490, p<0.001), delta E velocity OR 1.822 (1.179–2.360, p<0.001), delta t-IVT OR 1.406 (1.180–2.180, p<0.001), and delta FT OR 1.911 (1.401–2.710, p=0.001), were the most powerful independent predictors of the presence of CAD, particularly when significant (>50%). Delta mean s' <5.0 was 85% sensitive, 89% specific with AUC 0.92. Respective values for delta E velocity <6.0 cm/s were 82%, 90% and 0.91; for delta t-IVT >4.5, 78%, 77% and 0.81 and for delta FT ≥150ms, 76%, 78% and 0.84 in predicating significant CAD. WMSI≥0.7 was 75% sensitive, 77% specific with AUC of 0.81 in predicting significant CAD. The accuracy of DSE was higher in significant CAD compared to insignificant CAD (80% vs 74%; p=0.03). Conclusions: Compromised LV longitudinal systolic function, lower delta E wave, prolonged t-IVT and increased WMSI were the most powerful independent predictors of the presence and significance of CAD. These finding strengthen the role of comprehensive DSE analysis in diagnosing ischaemic disturbances secondary to significant CAD. Funding Acknowledgement: Type of funding sources: None.